Pengaruh Kecerdasan Emosional Dan Komunikasi Interpersonal Terhadap Organizational Citizenship Behavior (Ocb) Organisasi Santri(Studi Kasus PPP. Al-Fathimiyyah Bahrul Ulum Tambakberas Jombang) - Septian Ragil Anandita; Della Rachmadani P. R; Khotim Fadhli (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to determine the influence of emotional intelligence and interpersonal communication on organizational citizenship behavior. The research method used is a quantitative method with a cross-section approach and data is obtained from the results of the distribution of questionnaires or questionnaires. The sampling technique used saturated sampling and the number of samples used was 60 respondents. In the hypothesis of this study, it is to determine the influence of independent and bound variables both partially and simultaneously, so that the tests that are rigorously tested are descriptive analysis of classical assumption tests and multiple linear regression analysis using the SPSS Statistics 23 application. The results of the study showed that: 1) Emotional intelligence had a positive but insignificant effect on the organizational citizenship behavior of the student organization 2) Interpersonal communication had a positive and significant effect on the organizational citizenship behavior of the student organization 3) Emotional intelligence and interpersonal communication had a simultaneous effect on the organizational citizenship behavior student organizations.